Deliberation in parliaments: a review of the empirical, rhetorical and systemic approaches - Rico Motos, Carlos (Revista de Sociologia e Política, 2020)
ABSTRACT Introduction: This essay discusses three different approaches to the study of deliberation in parliaments: empirical, rhetorical and systemic. Materials and Methods: Through a critical review of the scientific literature, this work addresses some conceptual and analytical problems of the empirical-quantitative strategies aimed at measuring parliamentary deliberation, emphasizing the utility of the rhetorical and systemic approaches to grasp the agonist component of parliamentary debates and also their embeddedness within the broader political system. Results: The paper shows that deliberative dynamics within the democratic chambers cannot be reduced to a formal, closed and quantifiable debate. Hence, it proposes an alternative model for the analysis of deliberative processes in this institution. Discussion: The heterogeneous nature of parliaments recommends studying the deliberative phenomenon in different moments and instances, which includes formal debates, closed door meetings and even informal exchanges outside the plenary and committees. This view challenges the dominance of the empirical-quantitative framing of parliamentary deliberation in the scientific literature and supports a more holistic research strategy based on the combination of the empirical, rhetorical and systemic approaches. KEYWORDS: parliaments; deliberation; rhetoric; Discourse Quality Index; literature review. O processo deliberativo nos parlamentos: uma revisão das abordagens empíricas, retóricas e sistêmicas RESUMO Introdução: Discutimos três abordagens diferentes para estudar o processo de deliberação nos parlamentos: empírica, retórica e sistêmica. Materiais e Métodos: Através de uma revisão crítica da literatura científica, abordamos alguns problemas conceituais e analíticos das abordagens empírico-quantitativas destinadas a mensurar a deliberação parlamentar, enfatizando a utilidade das abordagens retóricas e sistêmicas para apreender o componente conflitivo dos debates parlamentares e sua inserção no sistema político mais amplo. Resultados: A dinâmica deliberativa das câmaras democráticas não pode ser reduzida a um debate formal, fechado e quantificável. Por isso, propomos um modelo alternativo para a análise dos processos deliberativos. Discussão: A natureza heterogênea dos parlamentos recomenda analisar o fenômeno deliberativo em diferentes momentos e instâncias, que incluem debates formais, reuniões a portas fechadas e até trocas informais fora do plenário e das comissões. Essa visão desafia o predomínio do enquadramento empírico-quantitativo da deliberação parlamentar na literatura e defende uma estratégia de pesquisa mais holística, baseada na combinação das abordagens empírica, retórica e sistêmica. PALAVRAS-CHAVE: parlamentos; deliberação; retórica; Índice de Qualidade do Discurso; revisão da literatura.